Pengaruh Tingkat Pendapatan, Penurunan Tarif, Dan Perubahan Cara Pembayaran Terhadap Kepatuhan Wajib Pajak UMKM Masa Pandemi Covid-19 - Lutfah Fadilah; Asrofi Langgeng Noermansyah; Krisdiyawati Krisdiyawati (Owner : Riset dan Jurnal Akuntansi, 2021)
This study aims to determine the effect of income levels, tariff reductions and changes in payment methods on MSME taxpayer compliance during the COVID-19 pandemic. Data collection techniques used questionnaires, observations, interviews, documentation and literature studies. The population in this study were all MSME taxpayers registered at KPP Pratama Tegal. The number of samples used as many as 50 respondents with the sampling method using purposive sampling method. The data analysis method used multiple linear regression analysis. The results of testing the first hypothesis show that the income level variable has an effect on MSME taxpayer compliance during the covid-19 pandemic. This shows that the higher the level of income received, the greater the compliance of MSME taxpayers. The results of testing the second hypothesis show that the rate reduction variable has no effect on MSME taxpayer compliance during the covid-19 pandemic. This shows that someone who does not comply with his obligations as a taxpayer, then even a low tax rate does not affect the level of compliance. The results of testing the third hypothesis show that the variable changes in payment methods affect MSME taxpayer compliance during the covid-19 pandemic. This means that changes in the method of paying taxes can improve MSME taxpayer compliance so that the easier the tax payment method used, the MSME taxpayer compliance will increase.